2012
DOI: 10.1007/s11046-012-9572-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Chlorate Inhibition of Chaetomium globosum Germination, Hyphal Growth, and Perithecia Synthesis

Abstract: Chaetomium globosum Kunze:Fr is a dermatophytic, dematiaceous fungus that is ubiquitous in soils, grows readily on cellulolytic materials, and is commonly found on water-damaged building materials. Chlorate affects nitrogen metabolism in fungi and is used to study compatibility among anamorphic fungi by inducing nit mutants. The effect of chlorate toxicity on C. globosum was investigated by amending a modified malt extract agar (MEA), oat agar, and carboxymethyl cellulose agar (CMC) with various levels of pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…To study the involvement of lipoxygenase in 3 L=O * formation, the effect of lipoxygenase inhibitor catechol on ultra-weak photon emission was studied in WT Arabidopsis leaves. It is well established that binding of catechol to the ferric non-heme iron of lipoxygenase leads to inactivation of the enzyme active site 34 . Figure 2 shows a photograph (D) and two-dimensional imaging of ultra-weak photon emission (E) measured in wounded Arabidopsis leaves in the absence (left) and presence (right) of catechol.…”
Section: Resultsmentioning
confidence: 99%
“…To study the involvement of lipoxygenase in 3 L=O * formation, the effect of lipoxygenase inhibitor catechol on ultra-weak photon emission was studied in WT Arabidopsis leaves. It is well established that binding of catechol to the ferric non-heme iron of lipoxygenase leads to inactivation of the enzyme active site 34 . Figure 2 shows a photograph (D) and two-dimensional imaging of ultra-weak photon emission (E) measured in wounded Arabidopsis leaves in the absence (left) and presence (right) of catechol.…”
Section: Resultsmentioning
confidence: 99%
“…This saprophytic fungus primarily resides in soil and decaying humus. It causes soft rot and decomposes plant cells using hyphal cellulase activity, which performs best at high tropical temperatures [29]. The fungus also changes the colour of paper.…”
Section: Fungi Decay and Termite Damage Testmentioning
confidence: 99%
“…So far, no literature has been encountered associating Chaetomium globosum with plantain. However, Biles et al (2012) reported that Chaetomium globosum decomposes plant cells using hyphal cellulase activity. More to that, they are known to cause soft rot rather than brown rot, C. globosum plant decomposition leaves behind lignin residues (Biles et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, Biles et al (2012) reported that Chaetomium globosum decomposes plant cells using hyphal cellulase activity. More to that, they are known to cause soft rot rather than brown rot, C. globosum plant decomposition leaves behind lignin residues (Biles et al, 2012). Therefore, C. globosum could also be a contributing factor to the corm rot observed in the macro propagators.…”
Section: Discussionmentioning
confidence: 99%